Numerical investigation of the bending, torsional, and hydrostatic pressure responses of hybrid kenaf/flax/glass fiber composite shell structures for unmanned maritime vehicles - Huang, Yang; Sultan, Mohamed Thariq Hameed; Łukaszewicz, Andrzej; Józwik, Jerzy; Latiff, Khairunnisak (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Recently, with concern for the environment and the request for sustainable materials, more researchers and manufacturers have focused on the substitute solution of synthetic fiber reinforcement composites in industry applications. Green hybrid composites with natural components can present excellent sustainability, possess superior mechanical behavior, and reduce hazards. Hybridization technology allows new materials to inherit their raw materials’ characteristics and generate new properties. The current study designed novel double-walled shell structures (DS1R4L, DS2R8L, and DS5R12L), containing two thin walls and different numbers of ring and longitudinal stiffeners, as unmanned maritime vehicle (UMV) components. A normal single-walled cylindrical shell was used as a control. These models will be made of hybrid kenaf/flax/glass-fiber-reinforced composites, GKFKG and GFKFG, created in the ANSYS Workbench. The mechanical responses (deformation, stress, and strain characteristics) of models were examined under three loading conditions (end force, end torque, and hydrostatic pressure) to evaluate the influence of both material change and structural configuration. Compared to the single-walled structure, the double-walled configurations display minimized deflection and torsional angle. Moreover, GKFKG-made structures are better than GFKFG-made ones. The research contributes positively to advancing the application of hybrid kenaf/flax/glass-fiber-reinforced composites in UMV structures and promotes the development of green sustainable materials.